Enhancing Learner Participation in Developing Speaking Skills: A Study on Promoting Learning Autonomy through E-Learning Implementation - Manshur, Umar; Wijaya, Mu'alim; Zahirah, Lu'luah (JURNAL IJ-ATL, 2022)
This research deals with students’ participation in upgrading speaking skills. An attempt to develop autonomy through online learning applications. The purpose of this research is to describe the autonomy of practicing Arabic speaking that can be upgraded automatically. The research methodology used in this research is both qualitative and quantitative research so that the research results are hopefully more comprehensive. Quantitative data were extracted using a questionnaire considering the following criteria: student awareness, independent effort, independent activity, reference, motivation, and use of learning technology. While qualitative data were collected through interviews in order to measure students’ opinions on learning autonomy. The results of the research are that the independence of learning "self-learning" that students do outside the classroom was mostly at medium and high levels and can be described as follows: awareness at a high level of 3.67, independent effort at a medium level of 3.23, independent activity at a level of 3.00, self-confidence at a medium level of 3.42, then use of educational technology at a high level of 4.16. Students who obtain a high level benefit from educational technology. As for those who are weak in motivation, they were at a low level and did not respect themselves in learning the Arabic language.